Reaksi Pasar Atas Pengumuman Corporate Governance Perception Index - Putra, I Gede Krisna Dharma; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
CGPI is the result of research from the Indonesian Institute for Corporate Governance (IICG) in collaboration with SWA magazine. This study aims to determine the reaction of the capital market on the CGPI announcement. The research was conducted at the company surveyed by CGPI for the period 2013-2016 by accessing the Indonesia Stock Exchange, IICG, Yahoo finance and SWA magazines. The population in this study were the companies surveyed by the Corporate Governance Perception Index (CGPI) for the period 2013-2016. The number of samples taken was 61 using the purposive sampling method. The data analysis technique used is the one sample t-test. Based on the results of the analysis, it was found that during the seven days of stock trading around the announcement of the Corporate Governance Perception Index (CGPI) without involving the comfounding effect (other announcements) there was no market reaction around the CGPI announcement date. Keywords: Corporate Governance Perception Index (CGPI), abnormal return, market reaction